Unresponsive Patient in the Post Anesthesia Care Unit - Christina Spofford; David Easker (Association of American Medical Colleges, 2015)
Abstract Anesthesia providers are required to provide care across the spectrum of the perioperative period. This includes preoperative evaluation and also postoperative care. This simulation series helps learners explore a common problem in the recovery room and consider diagnoses and strategies for dealing with it. Specifically, this simulation consists of four scenarios dealing with the unresponsive patient in the postanesthesia recovery unit (PACU). The front story of the patient is nearly identical for the four scenarios, but there are four possible causes to be explored. These can be done in sequence on the same day or on different days, depending on the time available. It functions as a tool for training, evaluating, and reinforcing material learned in the classroom and operating room, and is applicable for trainees at many different levels. This training module has the potential to identify weaknesses in a learner's approach to care within the postoperative period, which is a skill examined by the American Board of Anesthesiology Oral Exam. At our institution, we have found that both resident and student nurse anesthetists had some background and approach to the care of these simulated patients, but did not fully understand the systems limitations or how to fully integrate care across specialties.